2019
DOI: 10.31234/osf.io/8mpd2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replication of a tri-level model of anxiety and depression in a sample of young adults

Abstract: The wide array of symptoms of unipolar depressive and anxiety disorders has raised questions about the relationship between these disorders, and factor analysis provides one approach to examining these relationships. In this paper, we replicate the tri-level model of symptoms of anxiety and depression first proposed by Prenoveau et al. (2010) in a sample of young adults selected to vary in their risk for psychopathology. In the tri-level model, symptom-specific items load on three factors arranged in a bifacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Prior to the analysis relating to the experimental task described here, confirmatory factor analysis (CFA) was conducted to test whether the tri-level symptom model (Prenoveau et al, 2010;Prenoveau, Haimann and Zinbarg, in preparation) provided a good fit to the selfreported symptom data in the current sample provided at the time of the behavioural testing session. These analyses are described in full in Kramer et al (2019, April 3). In brief, the CFA was conducted using Mplus version 8 statistical software treating all items as categorical using robust weighted least squares estimation (WLSMV) using all available information (i.e., accommodating missing data).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the analysis relating to the experimental task described here, confirmatory factor analysis (CFA) was conducted to test whether the tri-level symptom model (Prenoveau et al, 2010;Prenoveau, Haimann and Zinbarg, in preparation) provided a good fit to the selfreported symptom data in the current sample provided at the time of the behavioural testing session. These analyses are described in full in Kramer et al (2019, April 3). In brief, the CFA was conducted using Mplus version 8 statistical software treating all items as categorical using robust weighted least squares estimation (WLSMV) using all available information (i.e., accommodating missing data).…”
Section: Discussionmentioning
confidence: 99%
“…Trilevel model factor scores were generated from 101 questionnaire items selected from self‐report symptom measures of anxiety and depression (for details, see Kramer et al, 2019; Young et al, 2020; and Table S1). As reported elsewhere (Kramer et al, 2019; Young et al, 2020), the CFA identified dimensions of general distress, fears and anhedonia‐apprehension, similar to findings in previous work. We extracted factor score estimates for these dimensions from the trilevel model for use in analyses presented here.…”
Section: Methodsmentioning
confidence: 99%
“…We extracted factor score estimates for these dimensions from the trilevel model for use in analyses presented here. Factor score estimates in the full BrainMAPD sample ( N = 336; Kramer et al, 2019; Young et al, 2020) were quasi‐orthogonal and can consequently be considered statistically independent. Furthermore, within the sample reported here ( n = 101) factor score estimates were not significantly correlated with each other (general distress and fears, r (101) = .11, p = .277; general distress and anhedonia‐apprehension, r (101) = −.07, p = .480; fears and anhedonia‐apprehension, r (101) = .13, p = .205).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address depression symptoms we capitalized on the availability of participants' individual scores on factors of a Tri-level model of anxiety and depression (Kramer et al, 2019;Prenoveau et al, 2010) which identifies three factors that capture the structure of depression and anxiety at differing levels of breadth: a broad general distress factor, two intermediate factors capturing specific differences between fear-and misery-based disorders (e.g., a "Fears" factor and an "Anhedonia-Apprehension" factor), and narrower disorder-specific factors that may delineate among depression and anxiety diagnoses (see online supplemental materials for factor analytic methods of the parent study). Analyses utilized participants' scores on the Anhedonia-Apprehension factor, shown in the parent study sample to carry the highest (negative) loadings of self-report items related to positive affect (see Kramer et al, 2019 for details on factor items).…”
Section: Mood Symptomsmentioning
confidence: 99%